Development of functional markers for peroxidase activity genes TaPod-7AS and TaPod-4AL in wheat - Xinyuan Liu; Yukun Cheng; Hongwei Geng; Yi Ren; Junmei Cao; Bin Bai; Yating Xue (BMC Genomics)
Abstract Grain peroxidase (POD) has a pivotal role in determining wheat flour color and end-use products. High POD activity in wheat grains can improve the whiteness and commercial value of flour. The POD genes TaPod-7AS and TaPod-4AL have high effects on POD activity in wheat. Function marker for POD genes can be used to improve flour color attributes accurately and efficiently in wheat molecular breeding. Here, wheat POD genes TaPod-7AS and TaPod-4AL were sequenced and characterized, gene expression analysis indicated that TaPod-7AS, TaPod-4AL, TaPod-D1 genes were highly expressed at 21 days after flowering. Function markers POD-7AS1 and POD-7AS2 were developed for TaPod-7AS, amplifying 424-bp and 464-bp PCR fragments in the cultivars with low and high POD activities, respectively. The markers POD-4AL1 and POD-4AL2 for TaPod-4AL amplified 541-bp and 391-bp fragments in the cultivars with low and high POD activities, respectively. The functional markers were validated in a diverse panel of 268 winter wheat cultivars and advanced lines, indicating significant associations between genotypes and POD activity (P < 0.05). The genotypes with favorable alleles TaPod-7ASb/TaPod-4ALb/TaPod-D1b had higher POD activity (749.9 U.g-1.min-1) than those with alleles TaPod-7ASa/TaPod-4ALa/TaPod-D1a (mean POD activity 619.4 U.g-1.min-1).